Arthroscopy-assisted Minimally Invasive Tarsometatarsal and Lisfranc Arthrodesis. A Case Series - Angthong, Chayanin; Rajbhandari, Prasit; Veljkovic, Andrea (My University, 2024)
BACKGROUND: First tarsometatarsal arthrodesis is an effective procedure for the correction of hallux valgus deformities. Traditionally, first to third tarsometatarsal and Lisfranc arthrodesis is performed via an open approach. Little is known about the role of combined arthroscopic and minimally invasive techniques. MATERIAL AND METHODS: We present a case series of complicated hallux valgus deformities and other conditions managed using arthroscopically assisted minimally invasive arthrodesis. We first performed a minimally invasive surgical procedure that allowed easy and unhindered access for the introduction of an arthroscopic instrument over the joint surface. RESULTS: The mean Visual Analogue Score - Foot and Ankle and Short Form-36 scores indicated satisfactory and acceptable postoperative outcomes, respectively. The mean patient satisfaction score was 94.44 and the mean follow-up duration was approximately 17.7 months. CONCLUSION: The described procedure has been preliminarily shown to be useful in terms of its minimal invasiveness, reproducibility, safety, and effectiveness.
Keywords: hallux valgus; minimally invasive surgery; outcomes; tarsometatarsal joint